The Influence of Office Facilities on Employee Performance at the Sumpang Binangae Sub-district Office, Barru Regency - Sapitri, Nur Faidah; Isgunandar, Isgunandar; Nasir, Nasir (International Journal of Administration and Education, 2024)
Employee performance plays an important role in achieving agency goals, so this study is very important to identify factors that affect their performance. This study focuses on the impact of office facilities on employee performance at the Sumpang Binangae Village Office, Barru Regency. Using quantitative methodology, this study is descriptive. Permanent and non-permanent employees at the Sumpang Binangae Village Office, Barru Regency became the subjects of this study, with a total of fifty-two staff. Complete sampling was carried out, and data were collected through documentation, survey, and observation techniques. Data analysis was carried out using the SPSS 22 tool, including validity and reliability checks to validate the research findings. A descriptive and detailed data analysis approach was used to obtain results and draw conclusions from statistical analysis. This study found that workplace facilities significantly affect productivity. The coefficient of determination of 0.477 for R square indicates that office facilities contribute 47.7 percent to employee performance, while motivation and corporate culture contribute the remaining 52.3 percent. The results of the study indicate that the work environment has a major impact on productivity.